Agarose oligosaccharide- silver nanoparticle- antimicrobial peptide- composite for wound dressing. (1st October 2021) - Chen, Xiangyan; Li, Hongjin; Qiao, Xiaoni; Jiang, Tianze; Fu, Xue; He, Yue; Zhao, Xia
Abstract: Marine polysaccharides or oligosaccharides have potential to promote wound healing due to their biocompatibility and physicochemical properties. However, microbial infection delays wound healing process, and novel antimicrobial wound dressings are urgently needed. Here, agarose oligosaccharides (AGO) obtained from marine red algae were used as a reducing and stabilizer for green synthesis of silver nanoparticles (AgNPs), and further successfully connected with odorranain A (OA), one of antimicrobial peptides (AMPs), to obtain a novel composite nanomaterial (AGO-AgNPs-OA). Transmission electron microscopy (TEM) and Malvern particle size analyzer showed that AGO-AgNPs-OA was spherical or elliptic with average size of about 100 nm. Circular dichroism (CD) spectroscopy showed that AGO-AgNPs stabilized the α-helical structure of OA. AGO-AgNPs-OA showed stronger anti-bacterial activities than AGO-AgNPs, and had good biocompatibility and significant promoting effect on wound healing. Our data suggest that AMPs conjugated marine oligosaccharides and AgNPs may be effective and safe antibacterial materials for wound therapy. Highlights: AGO-AgNPs-OA combining AgNPs and AMPs were prepared in a simple and eco-friendly way. AGO-AgNPs-OA can stabilize the helical structure of OA peptide. AGO-AgNPs-OA have good antibacterial activity and promoting wound healing. AGO-AgNPs-OA can regulate inflammation, enhance collagen deposition and angiogenesis.